Macroeconomic determinants of unemployment in developed countries - ALASTAIR ABISHA, ONG HSIEN LERK (2024)
This study thoroughly investigates the macroeconomic determinants of unemployment in developed countries. The aim of this study is to understand the influence of independent variables (IV), including GDP, Inflation, Population and FDI have towards the dependent variable, unemployment. Data of 5 developed countries were collected and analyzed using econometric methods. The relationship of the independent variables and dependent variables were analyzed using the panel model which are POLS and Hausman test. The findings found that GDP and FDI have an insignificant relationship towards unemployment whereas inflation and population have a significant relationship towards unemployment. The results obtained offers solutions for policymakers to tackle the problem of unemployment.